Arthroscopic Assistance in Surgical Management of Distal Radius Fractures: A Systematic Review and Meta-analysis - Román-Veas, Javier; Gutiérrez-Espinoza, Héctor; Campos-Jara, Christian; Martínez-García, Darío (Journal of Wrist Surgery, 2022)
Background Wrist arthroscopy has become a commonly used tool for the management of adults with distal radius fractures (DRFs), although its implementation requires technical competence. This systematic review and meta-analysis appraised the available evidence concerning the contribution of wrist arthroscopy to the functional and radiological outcomes of patients with DRFs operated with arthroscopic assistance.Methods Randomized control trials were identified through five principal electronic databases on May 31, 2022: Web of Science, Scopus, EBSCO, Embase, and PubMed. Two authors independently performed the search and data extraction and assessed risk of bias (RoB) using the Cochrane RoB tool.Results A total of 1,780 relevant abstracts and citations were extracted in the preliminary search, which yielded 6 trials that met the eligibility criteria, and 3 studies were included in the quantitative synthesis. The overall pooled mean difference (MD) estimate showed no significant difference in the Disabilities of the Arm, Shoulder, and Hand scores between surgical groups with and without arthroscopic assistance (MD = 0.77 points, 95% confidence interval = −6.58 to 5.03, p = 0.79), with substantial heterogeneity (I2 = 85%).Conclusion There was low-quality evidence that wrist arthroscopy conveyed not clinically or statistically significant difference to functional outcomes of patients with DRFs. However, our findings are limited by the numbers of studies included and lack of long-term follow-up, although they do provide a good starting point for future quality research.
Keywords: arthroscopy; arthroscopy assistance; distal radius fracture; randomized controlled trial; meta-analysis